Impact of different climatic conditions on peak core temperature of elite athletes during exercise in the heat: a Thermo Tokyo simulation study - Teunissen, L. P.; Jansen, K. M.; Janssen, E.; Kingma, B. R.; De Korte, J. Q.; Eijsvogels, T. M. (BMJ Open Sport & Exercise Medicine, 2022)
Objectives To evaluate how separate and combined climatic parameters affect peak core temperature during exercise in the heat using computer simulations fed with individual data.